ADVANCES IN PHOTONUCLEAR REACTIONS, NEUTRON-INDUCED REACTIONS, AND ISOMERIC STATES: A COMPREHENSIVE LITERATURE REVIEW - Mukhammedov Umidjon,; Safarov Abror, (TADQIQOTLAR.UZ, 2024)
Abstract: This literature review delves into recent developments in the fields of photonuclear reactions, neutron-induced reactions, and isomeric states, which are pivotal for advancing our understanding of nuclear physics. Photonuclear reactions, initiated by high-energy photons interacting with atomic nuclei, are essential for probing nuclear structure and astrophysical processes. Neutron-induced reactions offer insights into nuclear models, reactor design, and neutron-rich nuclei. The study of isomeric states, characterized by long-lived nuclear excited states, reveals crucial information about nuclear structure and has applications in medical imaging and quantum computing. This review encompasses theoretical models, experimental techniques, and practical applications, highlighting significant advancements and their broader implications in nuclear science and technology.